ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INDEKS PEMBANGUNAN MANUSIA (IPM) KOTA SEMARANG - Panji Anoraga; Yanuar Rachmansyah (STIE Trisna Negara OKU Timur, 2022)
This study finds out how much influence the human development index (IPM) of Semarang City has. Development programs organized by the government should be able to consider and describe the status of human development as a whole and also clearly, using a holistic and integrated development framework design, by as well as for humans, through program interventions and activities in the fields of education, health and other basic social services. . HDI is made through a three-dimensional approach, namely a long and healthy life, knowledge, and a decent living. The 3 basic dimensions are translated into 4 (four) components, namely: Life expectancy (UHH), School obsolescence (HLS), School obsolescence (RLS); and the level of Per capita Expenditure / Purchasing Power Ability (PPP).